Sources, Dangers and Treatments of Oily Soil Pollutants in Iraq - Mutter, Ghazi M.; Lamy, Aqeel R. (International Journal of Integrated Engineering, 2014)
Oil pollution presents significant risks to living organism and human health because it can alter the ecosystem in rivers, seas, oceans, and pollutes air and soil. Oil, for example, can even reduce the efficiency of drinking water plants. Iraq suffers a lot from oil pollution as a result of wars that not only damage the oil infrastructures but also cause loss of thousand hectare of agriculture lands. In addition, oil pollution become primary factor that contribute to the electricity, fuel shortage and traffic jam problems. Oil pollution can be easily found in many parts of Iraq, even in main streets, houses and gardens due to the residents mismanagement and misuse of oily products. Therefore, the aim of this paper is to focus in detail about the sources and dangers of oil pollution on the environment and soil, as well as to provide some suggestions and measurements that can help in limiting the impact of oil pollution in Iraq.